A Study of Essential Oils from Patchouli (Pogostemon cablin Benth.) and Its Potential as an Antivirus Agent to Relieve Symptoms of COVID-19 - Nadia Isnaini; Khairan Khairan; Meutia Faradhilla; Elly Sufriadi; Vicky Prajaputra; Binawati Ginting; Syaifullah Muhammad; Raihan Dara Lufika (Universitas Syiah Kuala, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a new type of virus that attacks the respiratory system and has caused the global epidemic of coronavirus disease 2019 (COVID-19). Some persons who are infected with this virus develop symptoms ranging from a typical cold to fever to more severe illnesses, such as Severe Acute Respiratory Syndrome (SARS) and Middle East Respiratory Syndrome (MERS). The development of a SARS-CoV-2 vaccine is being actively researched but will likely take more than a year to become available to the general public. As a result, numerous researchers are actively extracting the components of active chemicals in herbal plants with antiviral potentials, such as patchouli (Pogostemon cablin Benth.). Patchouli essential oil, found in this Lamiaceae plant, has a wide range of effects, including antibacterial, antifungal, antioxidant, antimutagenic, anticancer, anti-inflammatory, and aromatherapy. More than 140 chemicals have been isolated and identified from the patchouli plant, including terpenoids, phytosterols, flavonoids, organic acids, lignins, alkaloids, glycosides, alcohols, and aldehydes. Patchouli essential oil is mainly composed of sesquiterpene molecules, most of which are patchouli alcohol. Essential oils derived from herbal plant extracts have also been shown to be potent antiviral agents against various viruses. The efficacy of patchouli essential oil, as well as its potential as an antiviral agent to treat SARSCoV-2, will be investigated in this review.